SOLUTIONS BASED ON SOCIAL PHILOSOPHICAL INTERPRETATION IN ELIMINATING SOCIAL CONFLICTS (E Global Congress, 2023)
In modern society, social conflicts are an integral part of life. Differences in opinions, values, interests and needs can lead to tensions and conflicts between people and groups. The solution of these conflicts requires a deep understanding of their causes and the search for constructive approaches to their settlement. One of these approaches is the use of socio-philosophical interpretation in resolving social conflicts.